Positive electrode material and preparation method thereof, and lithium ion battery

By applying the first and second coverings on the surface of the matrix material and the surface of the secondary particles of the high-nickel ternary positive electrode material, the problems of structural instability and capacity attenuation of the positive electrode material during the electrochemical cycle are solved, and its cycling performance and rate performance are significantly improved.

CN118299527BActive Publication Date: 2025-04-18SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311289625.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-18
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials have problems such as structural instability, fast capacity attenuation, deterioration of thermal performance and residual alkali during the electrochemical cycle, which limits their commercial application.

Method used

A positive electrode material is used, which includes secondary particles formed by aggregation of a plurality of primary particles, a first covering (such as lithium tungstate or lithium molybdate) on the surface of the matrix material, and a second covering (such as Al2O3, TiO2, etc.) is present on the surface of the secondary particles to avoid direct contact between the positive electrode material and the electrolyte, inhibit the spread of microcracks, and improve the conductivity of the particle body.

Benefits of technology

Effectively improve the structural stability and cyclic performance of the positive electrode material, reduce the overpotential of the battery electrode, reduce the residual alkali on the surface of the positive electrode material, and improve the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118299527B_ABST
    Figure CN118299527B_ABST
Patent Text Reader

Abstract

The present application relates to a positive electrode material and a preparation method thereof, and a lithium ion battery. The positive electrode material includes secondary particles, which are formed by agglomeration of a plurality of primary particles. The secondary particles include: a matrix material, whose general chemical formula is Li a Ni x Co y M z N b O 2 , wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; and a first coating located on the surface of the base material, the first coating includes lithium tungstate and / or lithium molybdate; the positive electrode material also includes a second coating located on the surface of the secondary particles, the second coating is located between and / or on the surface of the primary particles on the surface of the secondary particles; the second coating includes Al 2 O 3 、TiO 2 、MgO、CeO 2 、ZrO 2 and at least one of the corresponding lithium-containing metal compounds. The positive electrode material of the present application can reduce the overpotential in the battery electrode and improve its cycle performance and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and preparation methods thereof, and lithium ion batteries. Background Art

[0002] At present, high energy density, high operating voltage, long cycle and high safety are urgent requirements for the widespread and large-scale application of lithium-ion batteries. The positive electrode material has a direct and dominant impact on the performance of lithium-ion battery packs. The quality of its performance will directly affect the overall performance of lithium-ion batteries. Therefore, it is urgent to develop positive electrode materials with excellent performance. High-nickel ternary positive electrode material LiMO2 (where M is usually Ni, Co, Mn or Al, and the molar fraction of Ni is above 0.6) has a high specific capacity (200mAh g -1 ), high packing density and low cost make it one of the most feasible options. However, as the nickel content increases, its discharge capacity increases proportionally, but it is accompanied by a series of defects such as rapid capacity decay, unstable structure, deteriorated thermal performance and high residual alkali, which limits its commercial application.

[0003] The main reason for the decline in the performance of high-nickel ternary cathode materials is a series of harmful processes that occur during the electrochemical cycle, including phase changes in the bulk and surface, intergranular cracking of secondary particles, the formation and growth of the cathode electrolyte interface, and the consumption of precious liquid organic electrolytes, gas generation, and side reactions that cause transition metal dissolution. Doping and coating modification are one of the most commonly used methods to improve the performance of ternary materials. Coating modification can reduce the residual alkali on the surface of the material, effectively slow down the side reactions between the electrolyte and the surface of the material, and then inhibit the surface phase transformation and O2 release problems, thereby improving the structural stability of the material and increasing the material life.

[0004] Although the traditional coating can protect the base material, it still cannot solve the problem of intergranular cracking of secondary particles. Intergranular cracking of secondary particles will lead to the formation of microcracks, which will expose more active sites inside the particles to react with the electrolyte, further accelerate the decay of the positive electrode material structure, reduce the structural stability and cycle stability of the positive electrode material, and thus reduce the cycle performance of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode material and a preparation method thereof, and a lithium-ion battery. The positive electrode material provided in the present application has a first coating on the surface of its primary particles, and a second coating also exists between the primary particles and / or on the surface of the secondary particles of the positive electrode material, which can effectively avoid direct contact between the positive electrode material and the electrolyte, inhibit the expansion of microcracks, and improve the stability of the coating / main interface; it can improve the electrical conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time effectively reducing the residual alkali on the surface of the positive electrode material, improving the cycle performance and rate performance of the positive electrode material.

[0006] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising secondary particles, the secondary particles being agglomerated from a plurality of primary particles, the secondary particles comprising:

[0007] The matrix material has the general chemical formula Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; and

[0008] A first coating located on the surface of the base material, wherein the first coating comprises lithium tungstate and / or lithium molybdate;

[0009] The positive electrode material also includes a second coating located on the surface of the secondary particles, and the second coating is located between and / or on the surface of the primary particles on the surface of the secondary particles; the second coating includes at least one of Al2O3, TiO2, MgO, CeO2, ZrO2 and their corresponding lithium-containing metal compounds.

[0010] In some embodiments, the coating layer has a thickness of 3 nm to 30 nm.

[0011] In some embodiments, the particle size of the second coating is 10 nm to 100 nm.

[0012] In some embodiments, the mass percentage of the second coating in the positive electrode material is 0.05 wt % to 0.8 wt %.

[0013] In some embodiments, the coating thickness of the second coating is 2 nm to 40 nm.

[0014] In some embodiments, the specific surface area of ​​the positive electrode material is 0.2 m2 / g~1.3m 2 / g.

[0015] In some embodiments, the surface free lithium content of the positive electrode material is 500 ppm to 1300 ppm.

[0016] In some embodiments, the average particle strength of the positive electrode material is ≥45 MPa.

[0017] In some embodiments, the compaction density of the positive electrode material is 2.1 g / cm 3 ~4.6g / cm 3 .

[0018] In some embodiments, the tap density of the positive electrode material is 1.7 g / cm 3 ~4.1g / cm 3 .

[0019] In some embodiments, the ratio between the compaction density and the tap density of the positive electrode material is 1.05 to 1.3.

[0020] In some embodiments, the average particle size D50 of the positive electrode material is 9 μm to 20 μm.

[0021] In some embodiments, the peak intensity I of the (006) crystal plane of the positive electrode material measured by X-ray diffraction pattern is 006 , the peak intensity of (101) crystal plane I 101 and the peak intensity I of the (102) crystal plane 102 The relationship between satisfies: 0.6≤(I 006 +I 102 ) / I 101 ≤0.850.

[0022] In some embodiments, the peak intensity I of the (110) crystal plane of the positive electrode material measured by X-ray diffraction pattern is 110 The peak intensity I 108 The relationship between them satisfies: |I 110 -I 108 ∣=0.39~0.46.

[0023] In some embodiments, the positive electrode material satisfies the following formula: Y=P-kX, wherein Y represents the mass content of free lithium on the surface of the positive electrode material, X represents the specific surface area of ​​the positive electrode material, P represents the Y-axis intercept, and the value of P is 900-2270, and k represents the absolute value of the slope, and the value of k is 260-1960.

[0024] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0025] preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide;

[0026] Adding a matrix material to the mixed solution, performing a heating dispersion treatment and a drying treatment, to obtain a composite material, wherein the matrix material has a chemical formula of Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta;

[0027] The composite material is sintered in an oxygen-containing atmosphere to obtain a positive electrode material.

[0028] In some embodiments, the mass ratio of the lithium salt to the first metal oxide is 1:(1-3).

[0029] In some embodiments, the mass ratio of the lithium salt to the second metal oxide and / or the second metal hydroxide is 1:(0.5-3).

[0030] In some embodiments, the mixed solution further includes a solvent.

[0031] In some embodiments, the mixed solution further includes a solvent, and the mass ratio of the total mass of the lithium salt and the metal oxide to the solvent is 1:(2-6).

[0032] In some embodiments, the mixed solution further includes a solvent, and the solvent includes at least one of water, ethanol and acetone.

[0033] In some embodiments, the lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.

[0034] In some embodiments, the first metal oxide includes at least one of tungsten oxide and molybdenum oxide.

[0035] In some embodiments, the second metal oxide includes at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, and cerium oxide.

[0036] In some embodiments, the second metal hydroxide includes at least one of aluminum hydroxide, magnesium hydroxide, titanium hydroxide, zirconium hydroxide, and cerium hydroxide.

[0037] In some embodiments, the median particle size D50 of the matrix material is 9 μm to 18 μm.

[0038] In some embodiments, the mass ratio of the matrix material to the mixed solution is 1:(0.3-1.5).

[0039] In some embodiments, the heating dispersion treatment includes adding the matrix material to the mixed solution, and performing ultrasonic dispersion treatment and heating stirring treatment.

[0040] In some embodiments, the heating dispersion treatment includes adding the matrix material to the mixed solution, performing ultrasonic dispersion treatment and heating stirring treatment, and the frequency of the ultrasonic dispersion treatment is 50 Hz to 100 Hz, and the time is 10 min to 60 min.

[0041] In some embodiments, the heating dispersion treatment comprises adding the matrix material to the mixed solution, performing ultrasonic dispersion treatment and heating stirring treatment, and the heating stirring treatment is performed at a temperature of 60° C. to 100° C. and for a time of 1 h to 3 h.

[0042] In some embodiments, the drying process is performed at a temperature of 100°C to 200°C.

[0043] In some embodiments, the drying process lasts for 12 hours to 48 hours.

[0044] In some embodiments, the sintering temperature is 300°C to 800°C.

[0045] In some embodiments, the sintering time is 3 hours to 15 hours.

[0046] In some embodiments, the step of preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide and a solvent comprises adding the lithium salt to the solvent, heating and stirring at 40°C to 80°C to form a transparent solution, adding the first metal oxide thereto, continuing to heat and stir at 40°C to 80°C until a transparent solution is formed again, and then adding the second metal oxide and / or the second metal hydroxide thereto, and ultrasonically dispersing at 50Hz to 100Hz for 10min to 60min.

[0047] In some embodiments, the method further comprises adding Ni x Co y M z Oxide or Ni x Coy M z The hydroxide and the lithium source are mixed to obtain a mixture, and the mixture is sintered to obtain a matrix material, wherein M is Mn and / or Al.

[0048] In some embodiments, the mixing conditions for obtaining the mixture are: dry grinding at 10° C. to 50° C. for 0.3 h to 2 h.

[0049] In some embodiments, the sintering conditions for obtaining the matrix material are: pre-sintering the mixture at 400° C. to 600° C. for 3 h to 9 h in an oxygen-containing atmosphere, and then sintering at 650° C. to 950° C. for 8 h to 16 h.

[0050] In some embodiments, the sintering conditions for obtaining the matrix material are: pre-sintering the mixture at 400°C to 600°C for 3h to 9h in an oxygen-containing atmosphere, and then sintering at 650°C to 950°C for 8h to 16h, wherein the mass content of oxygen in the oxygen-containing atmosphere is ≥95%.

[0051] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.

[0052] In some embodiments, the amount of the lithium source added is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of Li is 1:(0.95-1.1).

[0053] In some embodiments, the mixture further includes a compound containing a doping element N, wherein N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti, and Ta.

[0054] In some embodiments, the mixture further includes a compound containing a doping element N, N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta, and the compound containing the doping element N includes at least one of an oxide of the N element and a hydroxide of the N element.

[0055] In some embodiments, the mixture further comprises a compound containing the doping element N, and the added amount of the compound containing the doping element N is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of N is 1:(0-0.4).

[0056] In a third aspect, the present application provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode plate, the positive electrode plate comprising the positive electrode material of the first aspect or the positive electrode material prepared by the method for preparing the positive electrode material of the second aspect.

[0057] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0058] The positive electrode material provided by the present application includes secondary particles formed by the agglomeration of multiple primary particles, and the surface of the base material has a first coating, which can effectively avoid direct contact between the positive electrode material and the electrolyte, and improve the interface stability between the first coating and the base material; the presence of the first coating can improve the conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time can effectively reduce the residual alkali on the surface of the positive electrode material, and significantly improve the rate performance of the positive electrode material; in addition, the presence of a second coating between the primary particles and / or on the surface of the surface layer of the secondary particles of the positive electrode material can further isolate the contact between the positive electrode material and the electrolyte, and inhibit the expansion of microcracks to improve the particle strength, improve the structural stability of the positive electrode material, and then improve the cycle performance of the positive electrode material. The two complement each other and jointly construct an integrated structure of the positive electrode material, giving the positive electrode material excellent cycle performance and rate performance.

[0059] The present application provides a method for preparing a positive electrode material, comprising preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide, wherein the lithium salt in the mixed solution reacts with the first metal oxide to form lithium metal acid, adding a matrix material to the mixed solution, and injecting the lithium metal acid in the mixed solution into the grain boundaries between the matrix materials at a zero equilibrium wetting angle, and during a heating, dispersion treatment and a drying treatment, the lithium metal acid coats the matrix material, and at the same time, the second metal oxide and / or the second metal hydroxide coats the matrix material to form a composite material; and sintering the composite material in an oxygen-containing atmosphere, and during the sintering process, surface defects of the positive electrode material can be repaired. The positive electrode material has a first coating, and a second coating also exists between the primary particles and / or on the surface of the secondary particles of the positive electrode material, which can effectively avoid direct contact between the positive electrode material and the electrolyte, further construct an integrated structure of the positive electrode material, inhibit the expansion of microcracks, and improve the stability of the coating / main interface; it can improve the conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time effectively reducing the residual alkali on the surface of the positive electrode material, improving the cycle performance and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0061] Figure 1 A process flow chart of the preparation of the positive electrode material provided in the embodiment of the present application;

[0062] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1 of the present application;

[0063] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present application;

[0064] Figure 4a This is the particle strength curve of the positive electrode material prepared in Example 1 of the present application;

[0065] Figure 4b This is the particle strength curve of the positive electrode material prepared in Comparative Example 1 of the present application;

[0066] Figure 5a This is a comparison diagram of the positive electrode material prepared in Example 1 of the present application before and after compression;

[0067] Figure 5b This is a comparison diagram of the positive electrode material prepared in Comparative Example 1 of the present application before and after compression;

[0068] Figure 6 The EIS curves of the positive electrode materials prepared in Examples 1, 5 and 6 of the present application;

[0069] Figure 7 This is the XRD diagram of the positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0070] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0071] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0073] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0074] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising secondary particles, the secondary particles being agglomerated from a plurality of primary particles, the secondary particles comprising:

[0075] The matrix material has the general chemical formula Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; and

[0076] A first coating located on the surface of the base material, wherein the first coating comprises lithium tungstate and / or lithium molybdate;

[0077] The positive electrode material also includes a second coating located on the surface of the secondary particles, and the second coating is located between and / or on the surface of the primary particles on the surface of the secondary particles; the second coating includes at least one of Al2O3, TiO2, MgO, CeO2, ZrO2 and their corresponding lithium-containing metal compounds.

[0078] It can be understood that the secondary particles are formed by the aggregation of multiple primary particles. Some primary particles are located inside the secondary particles and can be considered as the matrix of the secondary particles. Other primary particles are located outside the secondary particles and can be considered as the surface layer of the secondary particles, that is, the surface layer of the secondary particles in this application.

[0079] The positive electrode material provided by the present application includes secondary particles formed by the agglomeration of multiple primary particles, and the surface of the base material has a first coating, which can effectively avoid direct contact between the positive electrode material and the electrolyte, and improve the interface stability between the first coating and the base material; the presence of the first coating can improve the conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time can effectively reduce the residual alkali on the surface of the positive electrode material, and significantly improve the rate performance of the positive electrode material; in addition, the presence of a second coating between the primary particles and / or on the surface of the surface layer of the secondary particles of the positive electrode material can further isolate the contact between the positive electrode material and the electrolyte, and inhibit the expansion of microcracks to improve the particle strength, improve the structural stability of the positive electrode material, and then improve the cycle performance of the positive electrode material. The two complement each other and jointly construct an integrated structure of the positive electrode material, giving the positive electrode material excellent cycle performance and rate performance.

[0080] Specifically, the value of a can be, for example, 0.95, 0.98, 1.01, 1.02, 1.03, 1.05 or 1.1. When the molar content of Li in the positive electrode material is within the above range, the battery using the positive electrode material has a higher charge and discharge specific capacity; when the molar content of Li in the positive electrode material is low, Ni easily enters the Li layer, and the cation mixing is obvious, resulting in poor stability of the electrochemical cycle. When the molar content of Li in the positive electrode material is high, excess residual alkali will form on the surface of the material, and it is easy to form a jelly-like shape during the preparation of the slurry, affecting the coating effect; secondly, the effect of residual alkali on electrochemical performance is mainly reflected in the increase of irreversible capacity loss and the deterioration of cycle performance.

[0081] The value of x can be, for example, 0.6, 0.7, 0.8, 0.85, 0.86, 0.87, 0.88, 0.9, 0.92, 0.95, 0.97 or 0.99, the value of y can be, for example, 0.01, 0.05, 0.08, 0.1, 0.15, 0.16, 0.18, 0.2, 0.3, 0.37 or 0.39, the value of z can be, for example, 0.01, 0.05, 0.08, 0.1, 0.15, 0.16, 0.18, 0.2, 0.3, 0.37 or 0.39, etc., which are not limited here. When the total molar content of Ni, Co and M in the positive electrode material is within the above range, the battery has good electrochemical performance. When the total molar content of Ni, Co and M in the positive electrode material is small, the battery's first irreversible capacity is high, and its cycle and rate performance are poor; when the total molar content of Ni, Co and M in the positive electrode material is large, the battery's capacity is low and cannot meet the energy density requirements, affecting practical applications.

[0082] The value of b may be, for example, 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.35 or 0.39, etc., and is not limited here.

[0083] In some embodiments, the thickness of the first coating is 3 nm to 30 nm, specifically 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm or 30 nm, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0084] In some embodiments, the particle size of the second coating is 10 nm to 100 nm, specifically 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0085] In some embodiments, the mass proportion of the second coating in the positive electrode material is 0.05wt% to 0.8wt%, specifically 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt% or 0.8wt%, etc., and of course it can also be other values ​​within the above range, which are not limited here.

[0086] In some embodiments, the coating thickness of the second coating is 2nm to 40nm, specifically 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm or 40nm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. It can be understood that if the coating thickness of the second coating is too thin, the effect of resisting HF corrosion on the active material is poor, thereby affecting the cycle performance of the positive electrode material; if the coating thickness of the second coating is too thick, it will hinder the Li + diffusion, leading to higher Li + The ion migration barrier further affects the rate performance and cycle performance of the positive electrode material. Controlling the coating thickness of the second coating within the above range can, on the one hand, effectively block the direct contact between the positive electrode material and the electrolyte, reduce the side reaction between the positive electrode material and the electrolyte, and on the other hand, increase the lithium ion migration rate, thereby improving the rate performance and cycle performance of the positive electrode material.

[0087] In some embodiments, the specific surface area of ​​the positive electrode material is 0.2 m 2 / g~1.3m 2 / g, specifically 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g or 1.3m 2 When the specific surface area of ​​the positive electrode material is controlled within the above range, it is beneficial to improve the cycle performance of the lithium battery made of the positive electrode material.

[0088] In some embodiments, the surface free lithium content of the positive electrode material is 500ppm to 1300ppm, specifically 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm or 1300ppm, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0089] In some embodiments, the average particle strength of the positive electrode material is ≥45MPa. The average particle strength of the positive electrode material can be 45MPa, 46MPa, 47MPa, 48MPa, 49MPa, 50MPa, 55MPa or 60MPa, etc., which is not limited here. When the average particle strength of the positive electrode material is controlled within the above range, the formation and expansion of microcracks can be reduced, the structural stability of the positive electrode material can be improved, and the cycle stability of the positive electrode material can be further improved.

[0090] In some embodiments, the compaction density of the positive electrode material is 2.1 g / cm 3 ~4.6g / cm 3 Specifically, the compaction density of the positive electrode material can be 2.1 g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 , 3g / cm 3 , 3.5g / cm 3 , 4g / cm 3 , 4.3g / cm 3 4.5g / cm 3 or 4.6g / cm 3 Etc., no limitation is made here.

[0091] In some embodiments, the tap density of the positive electrode material is 1.7 g / cm 3 ~4.1g / cm 3 , specifically 1.7 g / cm 3 , 2g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 , 3.5g / cm 3 , 4g / cm 3 or 4.1 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0092] In some embodiments, the ratio between the compaction density and the tap density of the positive electrode material is 1.05 to 1.3, specifically 1.05, 1.08, 1.1, 1.15, 1.2, 1.25 or 1.3, etc., and of course other values ​​within the above range, which are not limited here. Controlling the ratio between the compaction density and the tap density of the positive electrode material within the above range can improve the compactness between particles in the battery pole piece made of the positive electrode material, improve the mass per unit volume of the pole piece and the shear strength, thereby giving the battery high capacity and safety stability.

[0093] In some embodiments, the average particle size D50 of the positive electrode material is 9 μm to 12 μm, specifically 9 μm, 9.5 μm, 10 μm, 11 μm or 12 μm, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Controlling the particle size of the positive electrode material within the above range is conducive to improving the structural stability, thermal stability and long cycle stability of the positive electrode material.

[0094] In some embodiments, the peak intensity I of the (006) crystal plane of the positive electrode material measured by X-ray diffraction pattern is 006 , the peak intensity of (101) crystal plane I 101 and the peak intensity I of the (102) crystal plane 102 The relationship between satisfies: 0.6≤(I 006 +I 102 ) / I 101 ≤0.85. (I 006 +I 102 ) / I 101 The specific value of can be 0.6, 0.65, 0.7, 0.72, 0.75, 0.78, 0, 0.79, 0.8, 0.83 or 0.85, etc., and is not limited here.

[0095] It should be noted that when I 006 ,I 101 ,I 102 The relationship between satisfies: 0.6≤(I 006 +I 102 ) / I 101 When ≤0.85, it indicates that the positive electrode material has good hexagonal crystal structure order and the positive electrode material is a layered structure. + Occupies the 3b position, and transition metals such as Ni, Co, and Mn randomly occupy the 3a position. + and Ni 2+ Ions with similar radii tend to occupy each other's positions, forming the so-called cation mixing. When Ni atoms occupy the sites of the lithium layer, the intensity of the 101 peak decays rapidly, resulting in a decrease in the structural order of the positive electrode material.

[0096] When(I 006 +I 102 ) / I 101 When the value is greater than 0.85, the degree of cation mixing in the positive electrode material is high, the structural order of the material is reduced, and the lithium ion deintercalation of the material is hindered. The structural order of the positive electrode material includes the structural order inside and on the surface of the bulk material. The formation of residual alkali on the surface of the positive electrode material will lead to ion rearrangement on the surface of the material, thereby reducing the structural order of the material. However, appropriate residual alkali will help Li + diffusion, promoting the improvement of electrochemical performance. Therefore, when (I 006 +I 102 ) / I 101 When the value is less than 0.6, although the material structure orderliness increases, the overall performance is not optimal. 006 +I 102 ) / I 101 The positive electrode material with a value between 0.6 and 0.85 has good structural stability and good overcharge resistance (such as Figure 7 shown).

[0097] In some embodiments, the peak intensity I of the (110) crystal plane of the positive electrode material measured by X-ray diffraction pattern is 110 The peak intensity I 108 The relationship between them satisfies: |I 110 -I 108 ∣=0.39~0.46. ∣I 110 -I 108 The specific value of | can be 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45 or 0.46, etc., which is not limited here. 108 -I 110 When the value of | is within the above range, such as Figure 7 As shown in the figure, the (108) and (110) diffraction peaks split significantly, indicating that the positive electrode material forms a better layered structure, which can promote the Li + The rapid deintercalation in the bulk structure and surface layer endows the cathode material with high rate performance and better kinetic stability.

[0098] In some embodiments, the positive electrode material satisfies the following formula: Y=P-kX, wherein Y represents the mass content of free lithium on the surface of the positive electrode material, X represents the specific surface area of ​​the positive electrode material, P represents the Y-axis intercept, and the value of P is 900-2270, and k represents the absolute value of the slope, and the value of k is 260-1960.

[0099] It should be noted that the surface free lithium of the positive electrode material mainly comes from the residual alkali on the surface of the material, and the formation of the surface residual alkali will cause the ions on the surface of the material to rearrange, thereby reducing the structural order of the material. In the linear equation of the specific surface area and the surface free lithium content of the positive electrode material, the larger the specific surface area of ​​the positive electrode material, the less the surface free lithium content of the material. The positive electrode material has a large specific surface area (i.e., a porous structure) that provides a long and tortuous path, which can prevent the expansion of intercrystalline cracks to provide high capacity retention and fast charging capabilities, while relieving stress and avoiding the occurrence of particle crushing. Therefore, the positive electrode material with a specific surface area within a certain range that satisfies the formula has a high structural order at the same time, and can hinder the expansion of microcracks, which together give the material excellent performance, thereby improving the battery's cycle performance and rate performance.

[0100] Specifically, by fitting the mass content Y of the free lithium on the surface of the positive electrode material and the specific surface area X of the positive electrode material, a fitting curve equation between X and Y can be obtained, and the fitting curve equation is a linear equation Y=P-kX; by processing the fitting curve equation data, it can be obtained that its Y-axis intercept P is 900-2270, the absolute value of the slope k is 260-1960, and R 2 It is 0.73~0.98.

[0101] Specifically, the value of P can be 900, 1000, 1200, 1500, 1600, 1800, 2000, 2100, 2200, 2220, 2250 or 2270, etc., and is not limited here.

[0102] The specific value of k can be 260, 300, 350, 400, 500, 600, 800, 1000, 1200, 1500, 1600, 1800, 1900, 1920, 1950 or 1960, etc., and is not limited here.

[0103] R 2 The specific value of can be 0.73, 0.75, 0.78, 0.85, 0.88, 0.90, 0.92, 0.93, 0.95, 0.96 or 0.98, etc., which is not limited here. 2 Indicates the fitting effect between data, R 2 The closer it is to 1, the better the data fit is.

[0104] In some embodiments, the Pearson correlation coefficient between Y and X is -0.98, indicating that there is a negative correlation between the specific surface area of ​​the positive electrode material and the surface free lithium, that is, when the specific surface area of ​​the positive electrode material increases, the surface free lithium content of the positive electrode material decreases accordingly.

[0105] In a second aspect, the present application provides a method for preparing a positive electrode material, such as Figure 1 As shown, the following steps are included:

[0106] Step S10, preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide;

[0107] Step S20, adding a matrix material to the mixed solution, performing a heating dispersion treatment and a drying treatment to obtain a composite material containing a matrix, wherein the general chemical formula of the matrix material is Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta;

[0108] Step S30, sintering the composite material in an oxygen-containing atmosphere to obtain a positive electrode material.

[0109] The present application provides a method for preparing a positive electrode material, comprising preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide, wherein the lithium salt in the mixed solution reacts with the first metal oxide to form lithium metal acid, adding a matrix material to the mixed solution, and injecting the lithium metal acid in the mixed solution into the grain boundaries between the matrix materials at a zero equilibrium wetting angle, and during a heating, dispersion and drying process, the lithium metal acid and the matrix material are coated, and at the same time, the second metal oxide and / or the second metal hydroxide coat the matrix material to form a composite material; and sintering the composite material in an oxygen-containing atmosphere, and during the sintering process, surface defects of the positive electrode material can be repaired. The positive electrode material has a first coating, and a second coating also exists between the primary particles and / or on the surface of the secondary particles of the positive electrode material, which can effectively avoid direct contact between the positive electrode material and the electrolyte, further construct an integrated structure of the positive electrode material, inhibit the expansion of microcracks, and improve the stability of the coating / main interface; it can improve the conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time effectively reducing the residual alkali on the surface of the positive electrode material, improving the cycle performance and rate performance of the positive electrode material.

[0110] The preparation method of the present application is described in detail below with reference to the examples:

[0111] Before step S10, the method further includes: x Co y M z Oxide or Nix Co y M z The hydroxide and the lithium source are mixed to obtain a mixture, and the mixture is sintered to obtain a matrix material, wherein M is Mn and / or Al. 0.6≤x<1, 0<y<0.4, 0<z<0.4.

[0112] In some embodiments, the amount of the lithium source added is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of Li is 1:(0.95-1.1), specifically 1:0.95, 1:0.99, 1:1.01, 1:1.02, 1:1.03, 1:1.05, 1:1.06, 1:1.08 and 1:1.1, etc., are not limited here. Controlling the ratio of the sum of the molar contents of Ni, Co and M to the molar content of Li within the above range is beneficial to the formation of matrix material grains and the improvement of the electrochemical properties of the material. Preferably, the amount of the lithium source added is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of Li is 1:1.01.

[0113] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.

[0114] In some embodiments, the mixture further includes a compound containing a doping element N, wherein N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti, and Ta.

[0115] In some embodiments, the compound containing the doping element N includes at least one of an oxide of the element N and a hydroxide of the element N.

[0116] In some embodiments, the added amount of the compound containing the doping element N is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of N is 1:(0-0.4).

[0117] In some embodiments, the mixing conditions for obtaining the mixture are: dry grinding at 10°C to 50°C for 0.3h to 2h. The dry grinding temperature can be 10°C, 20°C, 30°C, 40°C, 50°C, etc., and of course it can be other values ​​within the above range. The dry grinding time can be 0.3h, 0.5h, 0.8h, 1h, 1.5h or 2h, etc., and of course it can be other values ​​within the above range.

[0118] In some embodiments, the sintering conditions for obtaining the matrix material are: pre-sintering the mixture at 400° C. to 600° C. for 3 h to 9 h in an oxygen-containing atmosphere, and then sintering at 650° C. to 950° C. for 8 h to 16 h.

[0119] Specifically, the temperature of the first stage of sintering can be 400°C, 420°C, 450°C, 470°C, 480°C, 500°C, 520°C, 550°C, 580°C and 600°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. The holding time of the first stage of sintering can be 3h, 3.5h, 4h, 5.5h, 6h, 7.5h or 9h, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0120] The second stage temperature of sintering can be 650°C, 720°C, 750°C, 770°C, 780°C, 800°C, 820°C, 850°C, 880°C and 920°C, etc., and of course it can be other values ​​within the above range, which is not limited here. The second stage holding time of sintering can be 8h, 10h, 12h, 12.5h, 13h, 15h or 16h, etc., and of course it can be other values ​​within the above range, which is not limited here.

[0121] In some embodiments, the sintering equipment includes a stationary box furnace or a roller hearth continuous furnace.

[0122] In some embodiments, the ready-made base material can also be directly purchased for coating and modification.

[0123] Step S10, preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide.

[0124] In some embodiments, the step of preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide comprises adding the lithium salt to a solvent, heating and stirring at 40°C to 80°C to form a transparent solution, adding the first metal oxide thereto, continuing to heat and stir at 40°C to 80°C until a transparent solution is formed again, and then adding the doped metal oxide and / or doped metal hydroxide thereto, and ultrasonically dispersing at 50Hz to 100Hz for 10min to 60min.

[0125] In some embodiments, the mass ratio of the lithium salt to the first metal oxide is 1:(1-3), specifically 1:1, 1:1.2, 1:1.5, 1:2, 1:2.3, 1:2.5 or 1:3, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0126] In some embodiments, the mass ratio of the lithium salt to the second metal oxide and / or second metal hydroxide is 1:(0.5-3), specifically 1:0.5, 1:0.8, 1:1, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5 or 1:3, etc., which is not limited here.

[0127] In some embodiments, the mixed solution further includes a solvent.

[0128] In some embodiments, the mass ratio of the total mass of the lithium salt and the metal oxide to the solvent is 1:(2-6), specifically 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0129] In some embodiments, the solvent includes at least one of water, ethanol, and acetone.

[0130] In some embodiments, the lithium salt includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.

[0131] In some embodiments, the first metal oxide includes at least one of tungsten oxide and molybdenum oxide.

[0132] In some embodiments, the second metal oxide includes at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, and cerium oxide.

[0133] In some embodiments, the second metal hydroxide includes at least one of aluminum hydroxide, magnesium hydroxide, titanium hydroxide, zirconium hydroxide, and cerium hydroxide.

[0134] Step S20, adding the composite material to the mixed solution, performing a heating dispersion treatment and a drying treatment to obtain a composite material containing a matrix, wherein the chemical formula of the composite material is Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z+b=1, 0≤b<0.4, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta.

[0135] In some embodiments, the median particle size D50 of the composite material is 9 μm to 18 μm, specifically 9 μm, 10 μm, 11 μm, 12 μm 13 μm, 14 μm 15 μm, 16 μm, 17 μm or 18 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Controlling the particle size of the composite material within the above range is conducive to improving the structural stability, thermal stability and long cycle stability of the positive electrode material.

[0136] In some embodiments, the mass ratio of the composite material to the mixed solution is 1:(0.3-1.5), specifically 1:0.3, 1:0.4, 1:0.5, 1:0.8, 1:1, 1:1.1, 1:1.2 or 1:1.3, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0137] In some embodiments, the heating dispersion treatment includes adding the composite material to the mixed solution, and performing ultrasonic dispersion treatment and heating stirring treatment.

[0138] In some embodiments, the frequency of the ultrasonic dispersion treatment is 50 Hz to 100 Hz, and the time is 10 min to 60 min.

[0139] Specifically, the frequency of the ultrasonic dispersion treatment can be 50 Hz, 60 Hz, 70 Hz, 80 Hz, 90 Hz or 100 Hz, etc., which is not limited here. The time of the ultrasonic dispersion treatment can be 10 min, 15 min, 20 min, 30 min, 40 min, 45 min, 50 min or 60 min, etc., which is not limited here.

[0140] In some embodiments, the heating and stirring treatment is performed at a temperature of 60° C. to 100° C. and for a time of 1 h to 3 h.

[0141] Specifically, the temperature of the heating and stirring treatment can be 60°C, 65°C, 70°C, 75°C, 80°C, 90°C or 100°C, etc., which is not limited here. The time of the heating and stirring treatment can be 1h, 1.2h, 1.5h, 1.8h, 2h, 2.5h or 3h, etc., which is not limited here.

[0142] In some embodiments, the drying temperature is 100°C to 200°C, specifically 100°C, 120°C, 130°C, 150°C, 160°C, 170°C, 180°C or 200°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0143] In some embodiments, the drying time is 12 h to 48 h, specifically 12 h, 15 h, 18 h, 20 h, 22 h, 24 h, 25 h, 28 h, 30 h, 35 h, 35 h, 40 h, 43 h, 45 h or 48 h, etc., and is not limited here.

[0144] Step S30, sintering the composite material in an oxygen-containing atmosphere to obtain a positive electrode material.

[0145] In some embodiments, the sintering temperature is 300°C to 800°C, and can be specifically 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0146] In some embodiments, the sintering time is 3 h to 15 h, specifically 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0147] In a third aspect, the present application provides a lithium-ion battery, comprising a positive electrode plate, a negative electrode plate, a separator, a non-aqueous electrolyte and a casing, wherein the positive electrode plate comprises a current collector and a positive electrode active material coated on the current collector, and the positive electrode active material comprises the positive electrode material as described above or the positive electrode material prepared by the method for preparing the positive electrode material as described above, as well as a conductive agent and a binder.

[0148] In some embodiments, the conductive agent is one of conductive carbon black, Ketjen black, graphite, and acetylene black.

[0149] In some embodiments, the binder is one of sodium carboxymethyl cellulose, cyclodextrin, and polyvinylidene fluoride.

[0150] In some embodiments, the solvent in the positive electrode active material is selected from one of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide.

[0151] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0152] Example

[0153] Example 1

[0154] (1) Weigh appropriate amounts of LiOH and binary material nickel-cobalt precursor Ni in a molar ratio of 1.04:1. 0.90 Co 0.10(OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of (OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders and grind them to obtain a mixture.

[0155] (2) The mixture was calcined in a muffle furnace at 550°C for 4 h, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 h. The sintering temperature was controlled at 750°C. The sintered matrix material was crushed to D 50 The particle size is about 11 μm, and the crushed material is stored in a polyethylene plastic bag and sealed with aluminum plastic film.

[0156] (3) In a stirrable water-washed reactor, 8 g of lithium hydroxide was added to 50 ml of deionized water. After heating and stirring at 60° C. to form a transparent solution, 10 g of WO 3 was weighed and added thereto. The heating and stirring at 60° C. were continued until a transparent solution was formed. Then, 9 g of TiO 2 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension.

[0157] (4) Weigh 100 g of the matrix material and add it to the suspension. After ultrasonic dispersion at 60 Hz for 45 min, heat and stir at 80 °C for 2 h to evaporate the water solvent. Heat in a vacuum drying oven at 100 °C for 24 h to obtain a composite material.

[0158] (5) The composite material was calcined at 550° C. in an oxygen atmosphere for 10 h to obtain a modified positive electrode material.

[0159] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-1, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0160] The thickness of the lithium tungstate coating layer is 6.3nm, the coating thickness of the TiO2 nanoparticles is 5.6nm, the average particle size D50 of the positive electrode material is 11.5μm, and the specific surface area is 0.69m 2 / g, the mass content of free lithium on the surface is 931ppm, and the positive electrode material satisfies the formula Y=1496.7-819.8X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0161] Figure 2This is a SEM image of the positive electrode material prepared in Example 1 of the present application, as shown Figure 2 As shown, there are coating layers and nano- and granular coatings on the surface of secondary particles in the positive electrode material, and there are nano-scale granular coatings between the primary particles.

[0162] Example 2

[0163] The difference from Example 1 is that (3) 8 g of lithium hydroxide was added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 10 g of WO3 was weighed and added thereto. The heating and stirring at 60° C. were continued until a transparent solution was formed. Then 9 g of MgO2 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension. The remaining operations were the same as those in Example 1.

[0164] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-2, the positive electrode material further includes MgO2 nanoparticles located on the surface of the secondary particles, and the MgO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0165] The thickness of the lithium tungstate coating layer is 6.6 nm, the coating thickness of the MgO2 nanoparticles is 6.1 nm, the average particle size D50 of the positive electrode material is 11.1 μm, and the specific surface area is 0.70 m 2 / g, the mass content of free lithium on the surface is 923ppm, and the positive electrode material satisfies the formula Y=1496.7-819.8X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0166] Example 3

[0167] The difference from Example 1 is that (3) 8 g of lithium hydroxide was added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 10 g of WO3 was weighed and added thereto. The heating and stirring at 60° C. were continued until a transparent solution was formed. Then 9 g of ZrO2 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension. The remaining operations were the same as those in Example 1.

[0168] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li1.00 Ni 0.88 Co 0.10 Al 0.02 O2-3, the positive electrode material further comprises ZrO2 nanoparticles located on the surface of the secondary particles, and the ZrO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0169] Among them, the thickness of the lithium tungstate coating layer is 6.1nm, the coating thickness of the ZrO2 nanoparticles is 5.7nm, the average particle size D50 of the positive electrode material is 11.8μm, and the specific surface area is 0.68m 2 / g, the mass content of free lithium on the surface is 935ppm, which approximately satisfies the formula Y=1496.7-826.0X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0170] Example 4

[0171] The difference from Example 1 is that (3) 8 g of lithium hydroxide was added to 50 ml of deionized water in a stirrable water-washed reactor device, heated and stirred at 60° C. to form a transparent solution, 10 g of WO3 was weighed and added thereto, and heating and stirring were continued at 60° C. until a transparent solution was formed, and then 9 g of Al(OH)3 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension. The remaining operations were the same as in Example 1.

[0172] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-4, the positive electrode material further comprises Al2O3 nanoparticles located on the surface of the secondary particles, and the Al2O3 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0173] Among them, the thickness of the lithium tungstate coating layer is 6.8nm, the coating thickness of the Al2O3 nanoparticles is 5.3nm, the average particle size D50 of the positive electrode material is 11.3μm, and the specific surface area is 0.70m 2 / g, the mass content of free lithium on the surface is 919ppm, and the positive electrode material satisfies the formula Y=1496.7-825.0X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0174] Example 5

[0175] The difference from Example 1 is that (5) the composite material is calcined at 700° C. in an oxygen atmosphere for 10 h to obtain a modified positive electrode material. The remaining operations are the same as in Example 1.

[0176] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-5, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0177] The thickness of the lithium tungstate coating layer is 6.1nm, the coating thickness of the TiO2 nanoparticles is 5.2nm, the average particle size D50 of the positive electrode material is 11.6μm, and the specific surface area is 0.35m 2 / g, the mass content of free lithium on the surface is 1210ppm, and the positive electrode material satisfies the formula Y=1496.7-819.1X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0178] Example 6

[0179] The difference from Example 1 is that (5) the composite material is calcined at 400° C. in an oxygen atmosphere for 10 h to obtain a modified positive electrode material. The remaining operations are the same as in Example 1.

[0180] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-6, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0181] The thickness of the lithium tungstate coating layer is 6.4 nm, the coating thickness of the TiO2 nanoparticles is 6.2 nm, the average particle size D50 of the positive electrode material is 11.2 μm, and the specific surface area is 0.89 m 2 / g, the mass content of free lithium on the surface is 750ppm, and the positive electrode material satisfies the formula Y=1496.7-838.9X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0182] Example 7

[0183] The difference from Example 1 is that (1) appropriate amounts of LiOH and binary material nickel-cobalt composite material Ni are weighed in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of (OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3 and then 0.90 Co 0.10 The mass ratio of (OH)2 to Zr(OH)4 is 350:1. Weigh an appropriate amount of Zr(OH)4, mix the four powders and crush and grind them to obtain a mixture. The rest of the operations are the same as in Example 1.

[0184] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.8838 Co 0.0971 Al 0.0177 Zr 0.0014 O2-7, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0185] The thickness of the lithium tungstate coating layer is 6.9 nm, the coating thickness of the TiO2 nanoparticles is 5.9 nm, the average particle size D50 of the positive electrode material is 11.7 μm, and the specific surface area is 0.71 m 2 / g, the mass content of free lithium on the surface is 910ppm, and the positive electrode material satisfies the formula Y=1496.7-826.6X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0186] Example 8

[0187] The difference from Example 1 is that NCM811 nickel cobalt lithium manganese oxide matrix material is purchased directly from the market, and the same scheme as steps (3), (4), and (5) is used to obtain the modified positive electrode material.

[0188] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Mn 0.10O2, the positive electrode material also includes TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0189] The thickness of the lithium tungstate coating layer is 6.9 nm, the coating thickness of the TiO2 nanoparticles is 6.0 nm, the average particle size D50 of the positive electrode material is 11.9 μm, and the specific surface area is 0.72 m 2 / g, the mass content of free lithium on the surface is 902ppm, and the positive electrode material satisfies the formula Y=1496.7-825.9X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0190] Example 9

[0191] The difference from Example 1 is that (3) 8 g of lithium hydroxide is added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 12 g of MoO3 is weighed and added thereto, and heating and stirring are continued at 60° C. until a transparent solution is formed. Then 9 g of TiO2 is added to the transparent solution, and ultrasonic dispersion is performed at 100 Hz for 30 minutes to obtain a suspension. The remaining operations are the same as those in Example 1.

[0192] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium molybdate coating layer located on the surface of the base material. The general chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-8, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0193] The thickness of the lithium molybdate coating layer is 6.8 nm, the coating thickness of the TiO2 nanoparticles is 5.4 nm, the average particle size D50 of the positive electrode material is 11.6 μm, and the specific surface area is 0.72 m 2 / g, the mass content of free lithium on the surface is 905ppm, and the positive electrode material satisfies the formula Y=1496.7-821.8X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0194] Example 10

[0195] The difference from Example 1 is that (3) 8 g of lithium hydroxide was added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 5 g of WO3 and 6 g of MoO3 were weighed and added thereto. The mixture was heated and stirred at 60° C. until a transparent solution was formed. Then 9 g of TiO2 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension. The remaining operations were the same as those in Example 1.

[0196] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium molybdate and lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-9, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0197] The thickness of the coating layer of lithium molybdate and lithium tungstate is 7.0nm, the coating thickness of TiO2 nanoparticles is 5.5nm, the average particle size D50 of the positive electrode material is 11.5μm, and the specific surface area is 0.71m 2 / g, the mass content of free lithium on the surface is 913ppm, and the positive electrode material satisfies the formula Y=1496.7-821.8X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0198] Embodiment 11

[0199] The difference from Example 1 is that (3) 8 g of lithium hydroxide was added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 10 g of WO3 was weighed and added thereto. The heating and stirring at 60° C. were continued until a transparent solution was formed. Then 75 g of TiO2 was added to the transparent solution, and ultrasonic dispersion was performed at 100 Hz for 30 min to obtain a suspension. The remaining operations were the same as those in Example 1.

[0200] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-10, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0201] Among them, the thickness of the lithium tungstate coating layer is 6.8nm, the coating thickness of the TiO2 nanoparticles is 39.6nm, the average particle size D50 of the positive electrode material is 11.5μm, and the specific surface area is 0.67m 2 / g, the mass content of free lithium on the surface is 939ppm, and the positive electrode material satisfies the formula Y=1494.7-829.3X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0202] Example 12

[0203] The difference from Example 1 is that (3) 8 g of lithium hydroxide is added to 50 ml of deionized water in a stirrable water-washed reactor device, and heated and stirred at 60° C. to form a transparent solution. Then 10 g of WO3 is weighed and added thereto, and heating and stirring are continued at 60° C. until a transparent solution is formed. Then 3 g of TiO2 is added to the transparent solution, and ultrasonic dispersion is performed at 100 Hz for 30 min to obtain a suspension. The remaining operations are the same as those in Example 1.

[0204] The positive electrode material prepared in this comparative example includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-11, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0205] The thickness of the lithium tungstate coating layer is 6.3 nm, the coating thickness of the TiO2 nanoparticles is 2.7 nm, the average particle size D50 of the positive electrode material is 11.0 μm, and the specific surface area is 0.69 m 2 / g, the mass content of free lithium on the surface is 927ppm, and the positive electrode material satisfies the formula Y=1494.7-822.7X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0206] Embodiment 13

[0207] Different from Example 1, (2) the mixture was calcined in a muffle furnace at 550°C for 4 h, ground into fine particles, and then transferred to a tube furnace in an oxygen atmosphere for high-temperature sintering for 14 h. The sintering temperature was controlled at 730°C. The sintered matrix material was crushed to D 50 The pulverized material was stored in a polyethylene plastic bag and sealed with an aluminum plastic film; the rest of the operations were the same as in Example 1.

[0208] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-12, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0209] Among them, the thickness of the lithium tungstate coating layer is 6.3nm, the coating thickness of the TiO2 nanoparticles is 5.5nm, the average particle size D50 of the positive electrode material is 11.9μm, and the specific surface area is 0.79m 2 / g, the mass content of free lithium on the surface is 850ppm, which approximately satisfies the formula Y=1497.7-820.0X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0210] Embodiment 14

[0211] Different from Example 1, (2) the mixture was calcined in a muffle furnace at 550°C for 4 h, ground into fine particles, and then transferred to a tube furnace in an oxygen atmosphere for high-temperature sintering for 14 h. The sintering temperature was controlled at 770°C. The sintered matrix material was crushed to D 50 The pulverized material was stored in a polyethylene plastic bag and sealed with an aluminum plastic film; the rest of the operations were the same as in Example 1.

[0212] The positive electrode material prepared in this embodiment includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-13, the positive electrode material further comprises TiO2 nanoparticles located on the surface of the secondary particles, and the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0213] The thickness of the lithium tungstate coating layer is 6.0 nm, the coating thickness of the TiO2 nanoparticles is 5.3 nm, the average particle size D50 of the positive electrode material is 11.7 μm, and the specific surface area is 0.60 m 2 / g, the mass content of free lithium on the surface is 1002ppm, which approximately satisfies the formula Y=1496.7-823.6X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0214] Comparative Example 1

[0215] (1) Weigh appropriate amounts of LiOH and binary material nickel-cobalt composite material Ni in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of (OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders and grind them to obtain a mixture.

[0216] (2) The mixture was calcined in a muffle furnace at 550°C for 4 h, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 h. The sintering temperature was controlled at 750°C. The sintered matrix material was crushed to D 50 The particle size is about 11 μm, and the crushed material is stored in a polyethylene plastic bag and sealed with aluminum plastic film.

[0217] (3) 100 g of the matrix material was weighed and added into 50 ml of deionized water. After ultrasonic dispersion at 60 Hz for 45 min, the mixture was heated and stirred at 80 °C for 2 h to evaporate the water solvent. The mixture was then heated in a vacuum drying oven at 100 °C for 24 h to obtain a composite material.

[0218] (4) The composite material was calcined at 550° C. in an oxygen atmosphere for 10 h to obtain a modified positive electrode material.

[0219] The chemical formula of the positive electrode material prepared in this comparative example is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-12; the surface of the positive electrode particles is not coated, the average particle size of the positive electrode material is 11.0μm, and the specific surface area is 0.70m 2 / g; the mass content of free lithium on the surface is 1033ppm, and the positive electrode material does not satisfy the formula Y=1494.7-826.6X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0220] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present application, as shown Figure 3 As shown, the surface of the primary particles of the positive electrode material and the spaces between the primary particles are relatively smooth, and there is no coating layer or coating on the surface of the positive electrode material.

[0221] Comparative Example 2

[0222] The difference from Example 1 is that (3) 8 g of lithium hydroxide is added to 50 ml of deionized water in a stirrable water-washed reactor device, and after heating and stirring at 60° C. to form a transparent solution, 10 g of WO3 is weighed and added thereto, and heating and stirring at 60° C. are continued until a transparent solution is formed. The remaining operations are the same as in Example 1.

[0223] The positive electrode material prepared in this comparative example includes secondary particles, which are formed by agglomeration of multiple primary particles. The secondary particles include: a base material and a lithium tungstate coating layer located on the surface of the base material. The chemical formula of the base material is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-13.

[0224] The thickness of the lithium tungstate coating layer is 6.1 nm, the average particle size D50 of the positive electrode material is 11.0 μm, and the specific surface area is 0.67 m 2 / g, the mass content of free lithium on the surface is 820ppm, and the positive electrode material does not satisfy the formula Y=1494.7-826.6X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0225] Comparative Example 3

[0226] The difference from Example 1 is that (3) 9 g of TiO2 is added to 50 ml of deionized water in a stirrable water-washing reactor and ultrasonically dispersed at 100 Hz for 30 min to obtain a suspension. The remaining operations are the same as in Example 1.

[0227] The positive electrode material prepared in this comparative example includes secondary particles, which are formed by agglomeration of a plurality of primary particles. The secondary particles include: a matrix material, the general chemical formula of which is Li 1.00 Ni 0.88 Co 0.10 Al 0.02 O2-14 and TiO2 nanoparticles located on the surface of the secondary particles, wherein the TiO2 nanoparticles are located between and / or on the surface of the primary particles on the surface of the secondary particles.

[0228] The coating thickness of TiO2 nanoparticles is 5.1nm, the average particle size D50 of the positive electrode material is 11.3μm, and the specific surface area is 0.68m 2 / g, the mass content of free lithium on the surface is 1123ppm, and the positive electrode material does not satisfy the formula Y=1494.7-826.6X, where X represents the specific surface area and Y represents the mass content of free lithium on the surface.

[0229] Test Method

[0230] (1) Test method for thickness of first coating:

[0231] The thickness of the first coating is measured using a transmission electron microscope (TEM) with a built-in ruler at a magnification of 50k to 100k.

[0232] (2) Testing method for particle size of the second coating:

[0233] The particle size of the second coating was measured using a scanning electron microscope (SEM) with a built-in ruler at a magnification of 20k to 100k.

[0234] (3) Test method for average particle size of positive electrode material:

[0235] The particle size distribution of the positive electrode particles dispersed in a certain aqueous solution was tested using a Malvern laser particle size analyzer 3000.

[0236] (43) Test method for specific surface area of ​​positive electrode material:

[0237] The specific surface area of ​​the positive electrode material is measured by the gas adsorption method. Specifically, Micromeritics Tristar II is used to perform N2 adsorption test and calculate the adsorption amount under different equilibrium pressures, and the isothermal adsorption line is obtained to calculate the specific surface area of ​​the positive electrode material.

[0238] (5) Test method for compaction density of positive electrode materials:

[0239] The compaction density of the positive electrode particles is measured by the American 4350CARVER compaction density meter. Specifically, a certain mass of positive electrode material powder sample is placed in a metal sleeve and the ratio of the mass of the sample to the compacted volume is measured after maintaining it under a certain pressure for a certain period of time.

[0240] (6) Test method for tap density of positive electrode material:

[0241] The tap density of the positive electrode particles is measured by BT-303, specifically, the mass per unit volume of the positive electrode material powder in the container after being tapped under specified conditions.

[0242] (7) Test method for average particle strength of positive electrode material:

[0243] The strength of the cathode particles was measured by a dynamic ultra-microhardness tester DUH-211S.

[0244] (8) Test method for free lithium content on the surface of positive electrode materials:

[0245] The residual alkali free lithium of the positive electrode material was determined by using a Mettler Toledo automatic potentiometric titrator G20S. Specifically, a hydrochloric acid standard titration solution was used on the automatic potentiometric titrator in an equivalence point titration mode. The OH in the sample was calculated based on the jump point and the amount of hydrochloric acid standard titration solution (0.025 mol / L) consumed. - and CO3 2- The content is then converted into surface free lithium content.

[0246] (9) Electrochemical performance test:

[0247] The positive electrode materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were assembled into button cells: 0.8 g of positive electrode material, 0.1 g of conductive carbon black and 0.1 g of polyvinylidene fluoride were weighed and put into a ball mill, 15 mL of N-methylpyrrolidone was added, and ball milling was performed to form a uniform positive electrode slurry, which was then evenly coated on an aluminum foil and vacuum dried at 80°C for 12 h to obtain a positive electrode sheet. The lithium sheet was used as the negative electrode and assembled into a 2016 button cell in a glove box.

[0248] In the discharge range of 3.0V-4.3V and the condition of 1C theoretical capacity of 250mAh / g, the battery was tested using the CT2001A battery testing system of Wuhan Blue Electric Electronics Co., Ltd. The test results are shown in Table 2.

[0249] Table 1 Physical and chemical properties of positive electrode materials prepared in various embodiments and comparative examples

[0250]

[0251]

[0252] Table 2 Electrochemical properties of the positive electrode materials prepared in each embodiment and comparative example

[0253]

[0254] As shown in Table 1 and Table 2, according to the test data of Examples 1 to 12, the positive electrode material includes secondary particles formed by the agglomeration of multiple primary particles, and the surface of the base material has a first coating, which can effectively avoid direct contact between the positive electrode material and the electrolyte, and improve the stability of the coating / main interface; the presence of the first coating can improve the conductivity of the particle body and enhance the lithium ion migration rate, thereby improving the electronic and lithium ion conductivity of the positive electrode material, reducing the overpotential in the battery electrode, and at the same time effectively reducing the residual alkali on the surface of the positive electrode material, significantly improving the cycle performance and rate performance of the positive electrode material; in addition, the presence of a second coating between the primary particles and / or on the surface of the surface layer of the secondary particles of the positive electrode material can further isolate the contact between the positive electrode material and the electrolyte, further construct the integration of the positive electrode material, and inhibit the expansion of microcracks, thereby improving the particle strength, further improving the structural stability of the positive electrode material, and thus improving the cycle performance of the positive electrode material.

[0255] Figure 4a , Figure 4b The particle strength curves of the positive electrode materials prepared in Example 1 and Comparative Example 1 of the present application are shown respectively. A controlled force is applied to the particles and their displacement is recorded. In the initial stage of the test, the displacement increases rapidly with the increase of the compression force, and then a slow growth of the displacement is observed. Finally, the particles break at the critical point, and the displacement increases sharply under almost constant stress. The particle strength is calculated by measuring the breaking force and cross-sectional area of ​​the particles. Figure 4a , Figure 4b As shown, since the positive electrode material of Example 1 has a first coating on the surface of its primary particles, and a second coating exists between the primary particles and / or on the surface of the secondary particles of the positive electrode material, the integrity and stability of the positive electrode material particles are enhanced, and the average particle hardness is stronger than that of the particles without a coating on the surface in Comparative Example 1.

[0256] Figure 5a , Figure 5b The following are comparison diagrams of the positive electrode materials prepared in Example 1 and Comparative Example 1 of the present application before and after compression, as shown in FIG. Figure 5a , Figure 5b As shown, the positive electrode material prepared in Comparative Example 1 has no coating on the surface, so the positive electrode particles are broken into dispersed small particles after compression, while the positive electrode material prepared in Example 1 can still maintain block shape after compression due to the presence of the surface coating, further indicating that the presence of the coating can further construct an integrated structure of the positive electrode material, inhibit the expansion of microcracks, enhance the particle strength, and thus improve the structural stability of the positive electrode material.

[0257] Figure 6 The EIS curves of the positive electrode materials prepared in Examples 1, 5 and 6 of the present application are shown in FIG. Figure 6It can be seen that with the increase of sintering temperature, the impedance of the positive electrode material decreases first and then increases, indicating that appropriate sintering temperature can repair the surface defects of the positive electrode material and thus reduce the impedance.

[0258] Through (I 006 +I 102 ) / I 101 The value is used to evaluate the orderliness of the hexagonal close-packed structure of the positive electrode material, and the structural orderliness is closely related to the performance of the positive electrode material. According to the test data of Examples 1, 5, and 6, under high temperature annealing (i.e., sintering of the composite material and cooling process after sintering), Li + Diffusion from the inside of the particle to the surface, with the increase of the secondary sintering temperature (i.e. the temperature at which the composite material is sintered), more Li diffuses from the inside of the particle to the surface. + , which leads to serious cation mixing inside the particles and poor structural order. When Ni atoms occupy the sites of the lithium layer, the intensity of the 101 peak decays rapidly, as shown in Table 1. Within a certain range, (I 006 +I 102 ) / I 101 The value gradually increases with the increase of secondary sintering temperature. In addition, the specific surface area of ​​the positive electrode material gradually decreases with the increase of secondary sintering temperature, that is, (I 006 +I 102 ) / I 101 The value is inversely proportional to the specific surface area of ​​the material. The larger the specific surface area, the more complete the contact between the positive electrode material and the electrolyte, which in turn leads to an increase in the capacity value, that is, (I 006 +I 102 ) / I 101 The value is inversely proportional to the capacity. Figure 7 The XRD diagram of the positive electrode material prepared in Example 1 of the present application is as follows: Figure 7 As shown in Figure 2, the (108) and (110) diffraction peaks are clearly split, indicating that the positive electrode material forms a better layered structure, that is, (I 006 +I 102 ) / I 101 The value is inversely proportional to the absolute value of the difference between the positions 2θ of the (108) and (110) diffraction peaks |110-108|. Therefore, there is an optimal treatment temperature that makes (I 006 +I 102 ) / I 101 The value reaches the optimal value, and the hexagonal close-packed structure of the positive electrode material is more ordered, which makes the positive electrode material have the best electrochemical performance.

[0259] In addition, a proper amount of porous structure (i.e., relatively large specific surface area) can effectively relieve stress and change the path of microcrack propagation, avoid particle crushing, and hinder the electrolyte from penetrating into the new microcrack interface and forming a passivation film, resulting in loss of active lithium ions and increased impedance. During high-temperature annealing (i.e., the process of sintering the composite material) and the subsequent cooling process, the Li ions diffused to the surface + It reacts with O2, CO2 and H2O molecules to form LiOH and Li2CO3 on the sample surface, which participates in the formation of residual lithium and causes ion rearrangement on the material surface, that is, the orderliness of the hexagonal close-packed structure of the positive electrode material is reduced, destroying the structural stability of the material, and then causing the capacity and capacity retention rate of the positive electrode material to decay rapidly. In addition, excessive residual alkali on the surface will affect the processing performance of the positive electrode material, causing the slurry to appear "jelly". In addition, free lithium on the surface helps Li + Diffusion, too low free lithium and too high specific surface area will lead to an increase in impedance, so there is an optimal free lithium content, that is, an optimal specific surface area, so that the positive electrode material has the best electrochemical performance. For example, the positive electrode materials in Examples 1, 5, and 6 have significantly different specific surface areas. Example 5 has the smallest specific surface area, which is not effective in relieving stress and changing the microcrack propagation path. At the same time, it has the highest residual alkali and high free lithium content. 006 +I 102 ) / I 101 The largest, that is, the lowest structural orderliness, resulting in the worst capacity and cycle performance among the three; Example 6 has the largest specific surface area. Due to the large contact area with the electrolyte, its capacity is higher. Although it can effectively relieve stress and change the microcrack propagation path, too many pores can easily cause crack penetration, ultimately resulting in a significant decrease in capacity retention rate; Example 1 has an appropriate specific surface area and free lithium content, so it has higher capacity, rate performance and cycle stability.

[0260] Compared with Example 1, the positive electrode material prepared in Example 11 has an increased coating thickness of the second coating in the positive electrode material. Although it can well block the direct contact between the positive electrode material and the electrolyte, increase the particle strength of the positive electrode material, and improve the structural stability of the positive electrode material, it will also hinder the Li + diffusion, leading to higher Li + The ion migration barrier further affects the rate performance and capacity retention of the positive electrode material.

[0261] Compared with Example 1, the positive electrode material prepared in Example 12 has a too thin coating thickness of the second coating, a slightly reduced particle strength of the positive electrode material, and a poor effect in resisting HF corrosion of the active material, thereby affecting the capacity retention rate of the material.

[0262] Compared with Example 1, the positive electrode material prepared in Example 13 has (I 006+I 102 ) / I 101 The value of is less than 0.6. Although the structural orderliness of the positive electrode material is increased, the structural stability of the positive electrode material is reduced compared with Example 1. The side reactions between the electrolytes of the positive electrode material are intensified, resulting in a decrease in the capacity and cycle performance of the positive electrode material.

[0263] Compared with Example 1, the positive electrode material prepared in Example 14 has (I 006 +I 102 ) / I 101 The value of |I in the positive electrode material is greater than 0.85, the degree of cation mixing inside the positive electrode material particles is high, and the structural order of the positive electrode material is reduced, resulting in the obstruction of lithium ion insertion and extraction in the positive electrode material; at the same time, |I 110 -I 108 The value of | is less than 0.39, the layered structure of the positive electrode material is weakened, and Li + The rapid deintercalation in the bulk structure and surface layer slows down, resulting in a decrease in the capacity and cycle performance of the positive electrode material.

[0264] Compared with Example 1, the positive electrode material prepared in Comparative Example 1 has no coating layer on its surface, the positive electrode material is in direct contact with the electrolyte, the side reaction between the positive electrode active substance and the electrolyte is serious, the surface structure of the material is destroyed, the secondary particles are prone to cracking between the crystals to form microcracks, and the expansion of the microcracks is difficult to inhibit. At the same time, the formed microcracks expose more active sites of the positive electrode material particles to undergo side reactions with the electrolyte, further accelerating the decay of the positive electrode material structure, resulting in a significant decrease in the strength of the positive electrode material particles, a decrease in the structural stability of the material, and further a decrease in the capacity decay and cycle performance of the material.

[0265] Compared with Example 1, the positive electrode material of Comparative Example 2 does not have a second coating added during the preparation process, and there is no second coating between the primary particles and / or on the surface of the surface layer of the secondary particles of the prepared positive electrode material. The strength of the positive electrode material particles is reduced, and the number of microcracks formed by intercrystalline cracking of the secondary particles increases, which intensifies the side reactions between the positive electrode material and the electrolyte, further accelerates the decay of the positive electrode material structure, and causes the overall structural stability and cycle stability of the material to decrease, thereby reducing the cycle performance of the lithium-ion battery.

[0266] Compared with Example 1, the first metal oxide is not added during the preparation process of the positive electrode material of Comparative Example 3, and the surface of the primary particles of the prepared positive electrode material does not have the first coating, which increases the direct contact between the positive electrode material and the electrolyte, and causes serious side reactions between the positive electrode material and the electrolyte, thereby reducing the electrical conductivity of the positive electrode material particles and the lithium ion migration rate, thereby reducing the electronic and lithium ion conductivity of the positive electrode material, increasing the overpotential in the battery electrode, and increasing the residual alkali on the surface of the positive electrode material, which reduces the cycle performance and rate performance of the positive electrode material.

[0267] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes secondary particles, wherein the secondary particles are formed by agglomeration of a plurality of primary particles, and the secondary particles include: The matrix material has the general chemical formula Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; and A first coating layer located on the surface of the base material, the first coating layer includes lithium tungstate and / or lithium molybdate, the lithium tungstate and / or the lithium molybdate are filled in the grain boundaries between the base materials, and the base material is a primary particle located inside the secondary particle; The positive electrode material further includes a second metal compound located on the surface of the secondary particles, the second metal compound being located on the surface of the secondary particles; the second metal compound includes at least one of Al2O3, TiO2, MgO, CeO2, ZrO2 and corresponding lithium-containing metal compounds; In the scanning electron microscope image of the positive electrode material at a 3k field of view, the second metal compound has a granular structure; the particle size of the second metal compound is 10 nm to 100 nm.

2. The positive electrode material according to claim 1, characterized in that It meets at least one of the following technical features: (1) The thickness of the first coating layer is 3 nm to 30 nm; (2) The mass proportion of the second metal compound in the positive electrode material is 0.05wt%~0.8wt%; (3) The coating thickness of the second metal compound is 2 nm to 40 nm.

3. The positive electrode material according to claim 1 or 2, characterized in that It meets at least one of the following technical features: (1) The specific surface area of ​​the positive electrode material is 0.2 m 2 / g~1.3m 2 / g; (2) The mass content of free lithium on the surface of the positive electrode material is 500ppm~1300ppm; (3) The average particle strength of the positive electrode material is ≥45MPa; (4) The compaction density of the positive electrode material is 2.1 g / cm 3 ~4.6g / cm 3 ; (5) The tap density of the positive electrode material is 1.7 g / cm 3 ~4.1g / cm 3 ; (6) The ratio between the compaction density and the tap density of the positive electrode material is 1.05 to 1.3; (7) The average particle size D50 of the positive electrode material is 9 μm to 20 μm; (8) The peak intensity I of the (006) crystal plane of the positive electrode material obtained by measuring the X-ray diffraction spectrum 006 , the peak intensity of (101) crystal plane I 101 and the peak intensity I of the (102) crystal plane 102 The relationship between satisfies: 0.6≤(I 006 +I 102 ) / I 101 ≤0.850; (9) The peak intensity I of the (110) crystal plane of the positive electrode material obtained by measuring the X-ray diffraction spectrum 110 The peak intensity I 108 The relationship between them satisfies: |I 110 -I 108 ∣=0.39~0.

46.

4. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material satisfies the following formula: Y=P-kX, wherein Y represents the mass content of free lithium on the surface of the positive electrode material, X represents the specific surface area of ​​the positive electrode material, P represents the Y-axis intercept, and the value of P is 900~2270, and k represents the absolute value of the slope, and the value of k is 260~1960.

5. A method for preparing the positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide, wherein the mass ratio of the lithium salt to the first metal oxide, the second metal oxide and / or the second metal hydroxide is 1:(1-3):(0.5-3); Adding a matrix material to the mixed solution, performing a heating dispersion treatment and a drying treatment, to obtain a composite material, wherein the matrix material has a chemical formula of Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, 0≤b<0.4, x+y+z+b=1, M is Mn and / or Al, and N includes at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; The composite material is sintered in an oxygen-containing atmosphere to obtain a positive electrode material.

6. The preparation method according to claim 5, characterized in that: It meets at least one of the following technical features: (1) The mixed solution further includes a solvent; (2) The mixed solution further includes a solvent, and the mass ratio of the total mass of the lithium salt and the first metal oxide to the solvent is 1:(2-6); (3) The mixed solution further comprises a solvent, wherein the solvent comprises at least one of water, ethanol and acetone; (4) The lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate; (5) The first metal oxide includes at least one of tungsten oxide and molybdenum oxide; (6) the second metal oxide comprises at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide and cerium oxide; (7) The second metal hydroxide includes at least one of aluminum hydroxide, magnesium hydroxide, titanium hydroxide, zirconium hydroxide, and cerium hydroxide; (8) The average particle size D50 of the matrix material is 9 μm to 18 μm; (9) The mass ratio of the matrix material to the mixed solution is 1:(0.3~1.5).

7. The preparation method according to claim 5, characterized in that: It meets at least one of the following technical features: (1) The heating and dispersing treatment includes adding the matrix material to the mixed solution, performing ultrasonic dispersing treatment and heating and stirring treatment; (2) The heating dispersion treatment includes adding the matrix material to the mixed solution, performing ultrasonic dispersion treatment and heating stirring treatment, wherein the frequency of the ultrasonic dispersion treatment is 50 Hz to 100 Hz and the time is 10 min to 60 min; (3) The heating and dispersing treatment includes adding the matrix material to the mixed solution, performing ultrasonic dispersing treatment and heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 60°C to 100°C and the time is 1h to 3h; (4) The drying temperature is 100°C to 200°C; (5) The drying time is 12h~48h; (6) The sintering temperature is 300°C to 800°C; (7) The sintering time is 3h~15h; (8) The step of preparing a mixed solution containing a lithium salt, a first metal oxide, a second metal oxide and / or a second metal hydroxide comprises adding the lithium salt to a solvent, heating and stirring at 40°C to 80°C to form a transparent solution, adding the first metal oxide thereto, continuing to heat and stir at 40°C to 80°C until a transparent solution is formed again, and then adding the second metal oxide and / or the second metal hydroxide thereto, and ultrasonically dispersing at 50 Hz to 100 Hz for 10 min to 60 min.

8. The preparation method according to claim 5, characterized in that: The method further comprises adding Ni x Co y M z Oxide or Ni x Co y M z The hydroxide and the lithium source are mixed to obtain a mixture, and the mixture is sintered to obtain a matrix material, wherein M is Mn and / or Al.

9. The preparation method according to claim 8, characterized in that: It meets at least one of the following technical features: (1) The mixing conditions for obtaining the mixture are: dry grinding at 10° C. to 50° C. for 0.3 h to 2 h; (2) The sintering conditions for obtaining the matrix material are as follows: pre-sintering the mixture at 400° C. to 600° C. for 3 h to 9 h in an oxygen-containing atmosphere, and then sintering at 650° C. to 950° C. for 8 h to 16 h; (3) The sintering conditions for obtaining the matrix material are as follows: pre-sintering the mixture at 400° C. to 600° C. for 3 h to 9 h in an oxygen-containing atmosphere, and then sintering at 650° C. to 950° C. for 8 h to 16 h, wherein the mass content of oxygen in the oxygen-containing atmosphere is ≥ 95%; (4) The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate; (5) The amount of the lithium source added is such that the ratio of the total molar content of Ni, Co and M to the molar content of Li is 1:(0.95-1.1); (6) The mixture further comprises a compound containing a doping element N, wherein N comprises at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta; (7) The mixture further comprises a compound containing a doping element N, wherein N comprises at least one of Zr, Mg, Sr, V, Y, Nb, B, S, Ba, Ti and Ta, and the compound containing the doping element N comprises at least one of an oxide of the element N and a hydroxide of the element N; (8) The mixture further comprises a compound containing the doping element N, and the added amount of the compound containing the doping element N is such that the ratio of the sum of the molar contents of Ni, Co and M to the molar content of N is 1:(0-0.4).

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode plate, and the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 4 or a positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN116207229A